PENDEKATAN KONSELING SPIRITUAL UNTUK MENGATASI BULLYING PADA SISWA MTS BUSTANUL ULUM MEMPAWAH TIMUR - Nurul Muftihah; Luhur Wicaksono; Yuline Yuline (Universitas Tanjungpura, 2021)
AbstractNot all behavior is self- or human-initiated, yet, bullying in the school environment is unavoidable. Bullying can be vocal or nonverbal. (1) What are the different types of bullying at MTs Bustanul Ulum Mempawah Timur? (2) What are the different types of bullying at MTs Bustanul Ulum Mempawah Timur? (2) Why is spiritual counseling provided at MTs Bustanul Ulum Mempawah Timur? (3) What role do BK teachers play at MTs Bustanul Ulum Mempawah Timur in spiritual counseling? This study intends to explain the types of bullying that occur among MTs Bustanul students The approach utilized was descriptive, and the research was conducted in the form of a survey. Three students and a BK teacher participated in this study. A qualitative technique is used in this research. Observation, interviews, and documentation were utilized to obtain data. Verbal bullying includes (1)swearing,(2)insulting,(3)labeling,(4)yelling, (5)humiliating in public, (6) accusing, and (7) slandering, according to the findings of the study. Religious therapies and scripture-based interventions are used in the approach. While BK teachers' primary responsibilities are to provide assistance, coaching/awards, enlightenment, role modeling, encouragement, and problem solving, in order to deliver a more accurate image in the future.Keywords: Bullying, Spiritual Counseling